Mali : First Review Under the Extended Credit Facility Arrangement, Request for a Waiver of Nonobservance of a Performance Criterion and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Mali's First Review Under the Extended Credit Facility Arrangement, Request for a Waiver of NonObservance of a Performance Criterion and Modification of Performance Criteria. Mali's economic growth has remained solid and the authorities have steadfastly implemented their revenue mobilization program and structural reforms are underway. Continued commitment to sound policies and reforms will be critical to achieving the program's objectives. Security and social conditions in Mali have steadily deteriorated in recent years, especially in the central and northern regions. Implementation of the 2015 peace agreement is challenging, rendering the return of effective state control to these regions difficult. The agreed fiscal framework reflects the impact of the difficult security situation on public finances. The overall fiscal deficit for 2020 has been increased to 3.5 percent of gross domestic product (GDP), from the previously agreed 3 percent of GDP, to prevent crowding out of social and development spending. The primary focus of the program remains on increasing revenue mobilization, strengthening cash management, improving governance, and pursuing the financial restructuring of the state electricity company. The mission paved the way for a governance assessment mission in early 2020.